ASSOCIATION OF SLEEP HYGIENE BEHAVIOR WITH SLEEP QUALITY IN OLDER ADULTS - Hijriana, Isni; Mardhiah, Ainal (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Background: Changes in sleep quality as a consequence of the aging process in the elderly can affect sleep quality. So older adults need to get good and appropriate sleep hygiene practices in order to increase sleep efficiency. Purpose: The purpose of this study was to examine the association between sleep hygiene behavior with sleep quality in older adults. Methods: This research is quantitative with the design used being a cross sectional study. The sample used in this research was 49 elderly people. Statistical analysis was performed using the Chi-Square test. Results: the results of bivariate analysis showed a p-value of 0.032 (p<0.05), indicating a statistically significant relationship between sleep hygiene behavior and sleep quality in the elderly. nursing interventions based on sleep hygiene education and modification can be an effective non-pharmacological approach to improving the aging population’s health and overall quality of life. Further research is recommended to explore additional factors such as environmental conditions, chronic health status, and social support that may influence sleep quality in the elderly. Conclusion: The importance of nursing services is that they can implement sleep hygiene practices which can be used as independent interventions by nurses in an effort to increase sleep efficiency in the aging population.